2006
DOI: 10.1021/jm060572f
|View full text |Cite
|
Sign up to set email alerts
|

Potent, Selective, and Orally Efficacious Antagonists of Melanin-Concentrating Hormone Receptor 1

Abstract: The high expression of MCH in the hypothalamus with the lean hypophagic phenotype coupled with increased resting metabolic rate and resistance to high fat diet-induced obesity of MCH KO mice has spurred considerable efforts to develop small molecule MCHR1 antagonists. Starting from a lead thienopyrimidinone series, structure-activity studies at the 3- and 6-positions of the thienopyrimidinone core afforded potent and selective MCHR1 antagonists with representative examples having suitable pharmacokinetic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…No specifics were provided, but it was reported that compound 6 was profiled against a battery of 7TM receptors, enzymes and ion channels with no significant off-target activity of note (Taveres et al, 2006b). They also reported an approximate 6700-fold selectivity for compound 7 binding to MCHR1 compared to the hERG patch clamp IC 50 (Tavares et al, 2006b).…”
Section: Development Of Small Molecule Mchr1 Antagonistsmentioning
confidence: 96%
“…No specifics were provided, but it was reported that compound 6 was profiled against a battery of 7TM receptors, enzymes and ion channels with no significant off-target activity of note (Taveres et al, 2006b). They also reported an approximate 6700-fold selectivity for compound 7 binding to MCHR1 compared to the hERG patch clamp IC 50 (Tavares et al, 2006b).…”
Section: Development Of Small Molecule Mchr1 Antagonistsmentioning
confidence: 96%
“…35 Condensation with 1,3-diaminopropane provided di-imine 4 as a reactive intermediate. Addition of commercially available tetrakis(acetonitrile)palladium(II) tetrafluoroborate gave complex 5 , with an immediate chromatic change of the reaction mixture from yellow to dark orange-brown.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of compound 96 in inducing weight loss was evaluated in a high fat (58% kcal of fat, Research Diets #D12331) DIO AKR/J mouse model described previously for compounds 10 and 65. During a 26-day treatment, oral administration of compound 90 at 1, 3 and 10 mg/kg once daily caused a sustained dosedependent weight loss of 4.8%, 9.4% and 16.9% respectively, relative to vehicle controls [33].…”
Section: Other Compounds: Quinolines and Related Heterocyclesmentioning
confidence: 94%